Microbial, physical, chemical and sensory properties of Minas Frescal Cheese with Inulin and gum Acacia (Acta Scientiarum. Technology, 2015)
Minas frescal cheese is a semi-skimmed product with high moisture and simple preparation and one of the most consumed in Brazil. Thus, the aim of this study was to combine the characteristics of inulin and gum acacia (by having fibers and being prebiotic) to produce a minas frescal cheese. Were evaluate the characteristics physical and chemical, microbial and sensory acceptance (hedonic scale) of each cheese. Three cheeses were prepared; one as a standard (QP) without inulin, and others with 0.49% (QI25) and 0.98% (QI50) inulin, the amount of gum acacia was maintained. The yield of the formulations with gum acacia and inulin were 9.76% for (QI25) and to 20.03% (QI50) higher than the standard sample. In relation to moisture content, samples containing inulin and gum acacia showed values greater than the standard sample. The sensory analysis indicated no differences between scores for color, aroma and texture, but significant differences were detected for flavor, in which (QI25) received the highest acceptance. Regarding the energy value, it was obtained 276 kcal (QP), 215 kcal (QI25) and 190 kcal (QI50). Therefore, the developed product presents satisfactory results for sensory, microbiological and physical-chemical analyses.